Planning Leadership in Managing Boarding School - Suranto, Andi; Putra, Alhadi Yan; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to examine the leadership role of the principal in managing the boarding school dormitories at SMA N 3 Kayuagung. The research was conducted using a qualitative approach and data was collected through interviews, observation and document analysis. The results of the study show that the principal’s leadership has an important role in creating a conducive environment, managing resources, developing student coaching programs, and building collaboration with various related parties. The school principal is also responsible for ensuring adequate facilities and infrastructure as well as the welfare of students in boarding school dormitories. This research provides insight into the importance of principal leadership in managing boarding school dormitories and provides suggestions for further development at SMA N 3 Kayuagung.